2011
DOI: 10.1002/glia.21201
|View full text |Cite
|
Sign up to set email alerts
|

Sox2 and Pax6 maintain the proliferative and developmental potential of gliogenic neural stem cells In vitro

Abstract: Radial-glia-like neural stem (NS) cells may be derived from neural tissues or via differentiation of pluripotent embryonic stem (ES) cells. However, the mechanisms controlling NS cell propagation and differentiation are not yet fully understood. Here we investigated the roles of Sox2 and Pax6, transcription factors widely expressed in central nervous system (CNS) progenitors, in mouse NS cells. Conditional deletion of either Sox2 or Pax6 in forebrain-derived NS cells reduced their clonogenicity in a gene dosag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 60 publications
4
57
0
Order By: Relevance
“…Sox2 has been shown previously to be essential for NS cell self-renewal in vitro (Gómez-López et al 2011). To test whether Foxg1 is required for in vitro self-renewal of NS cells, we derived a new NS cell line (termed FF) from the subventricular zone (SVZ) of a previously reported adult Foxg1 flox/flox mouse (Supplemental Fig.…”
Section: Loss Of Foxg1 Sensitizes Ns Cells To Astrocyte Differentiatimentioning
confidence: 99%
See 1 more Smart Citation
“…Sox2 has been shown previously to be essential for NS cell self-renewal in vitro (Gómez-López et al 2011). To test whether Foxg1 is required for in vitro self-renewal of NS cells, we derived a new NS cell line (termed FF) from the subventricular zone (SVZ) of a previously reported adult Foxg1 flox/flox mouse (Supplemental Fig.…”
Section: Loss Of Foxg1 Sensitizes Ns Cells To Astrocyte Differentiatimentioning
confidence: 99%
“…Previous studies have suggested that Sox2 is required for self-renewal of forebrain NS cells: Homozygous knockout by conditional deletion or CRISPR/Cas9 targeting is incompatible with colony formation (Gómez-López et al 2011;Bressan et al 2017). Here, CRISPR/Cas9 was used to mutate the single coding exon of SOX2 (Supplemental Fig.…”
Section: Genetic Ablation Of Foxg1 In Human Gns Cells Does Not Affectmentioning
confidence: 99%
“…Although this role of Pax6 could extend to other NSC populations, it appears to be modulated in a cell-and/ or genetic context. In fact, NSCs isolated from the embryonic forebrain of Pax6 conditional KO mice showed both reduced oligodendrocyte and astrocyte differentiation [20], whereas NSC/progenitors isolated from the embryonic forebrain of Pax6 heterozygous ( + /Sey) and homozygous (Sey/Sey) rats and mice developed excessive numbers of immature astrocytes [22,42].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in Pax6 homozygous mutant mice, an ectopic OB-like structure is formed [16,17]; whereas in humans, heterozygous mutations in Pax6 result in forebrain abnormalities [18]. In addition to these functions in brain patterning, Pax6 regulates the proliferation, self-renewal, differentiation, and apoptosis of embryonic NSCs and progenitor cells in multiple brain regions [19][20][21][22][23][24][25][26][27]. However, a few studies have evaluated the role of this TF in the maintenance and cell fate of NSCs from the adult SVZ and hippocampus [28][29][30], and no studies have yet been published on the putative role of Pax6 in NSCs isolated from the adult OB [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation